Relationship Between Placenta Previa And The Incidence Of Premature Labor At The Harapan Sehat Tentram Mother And Child Hospital - Nurhidayah, Nurhidayah; Suhartini, Suhartini; Lailaturohmah, Lailaturohmah (Innovative: Journal Of Social Science Research, 2021)
Placenta previa is a placenta that is abnormally located, namely in a segment under the uterus, so can cover all over opening road born . Placenta previa in premature pregnancy is more problematic because labor is forced due to heavy bleeding. This study aimed to determine the relationship between placenta previa and the incidence of premature labor. This research is correlational analytical research using a cross-sectional approach, the population of this study was 321 people, and the sample size was 38 people using a simple random sampling technique. The statistical test used in this research is the Chi-Square test with a significance p value of <0.05. The study results showed that the majority of mothers experiencing placenta previa were 23 respondents (60.5%), and the majority of mothers experiencing premature births were 21 respondents (55.3%). The results of the further analysis showed a significant relationship between placenta previa and premature labor in mothers giving birth at Harapan Sehat Trenggalek Mother and Child Hospital (p-value = 0.000; α <0.05).